Penguatan Kesadaran Bela Negara Pada Remaja Milenial Menuju Indonesia Emas - Siti Khairina Rahayu (PEDAGOGIKA, 2021)
Defending the state is not only the obligation of the TNI and Polri but the responsibility of all people, especially the millennial generation. As the nation's next generation, millennial youth have a great responsibility to determine the nation's future. State defense is an attitude and behavior that must be possessed by millennial youth to ensure the survival of the nation and state. Awareness and inculcation of the values ​​of defending the country are considered the best preventive concepts to fortify millennial youth to always have a sense of love, pride and loyalty to NKRI in the midst of today's developments. The purpose of this study includes how to strengthen awareness of defending the country in the millennial generation. This research is a qualitative research with a descriptive approach. The results of this study are that it is necessary to inculcate the values ​​of defending the state for millennial youth through formal and informal school facilities, lectures or examples by involving religious leaders or fighters, state defense training, seminars and FGDs, communication and information media/social media/internet media. by using struggle films, short videos, national songs, educational programs. In addition, awareness of defending the country can be raised by building national insight.